Toll-like receptor 4-mediated innate IL-10 activates antigen-specific regulatory T cells and confers resistance to Bordetella pertussis by inhibiting inflammatory pathology - LAVELLE, EDWARD; MILLS, KINGSTON (The American Association of Immunologists, 2003)
Signaling through Toll-like receptors (TLR) activates dendritic cell (DC) maturation and IL-12 production, which directs the induction of Th1 cells. We found that the production of IL-10, in addition to inflammatory cytokines and chemokines, was significantly reduced in DCs from TLR4-defective C3H/HeJ mice in response to Bordetella pertussis. TLR4 was also required for B. pertussis LPS-induced maturation of DCs, but other B. pertussis components stimulated DC maturation independently of TLR4. The course of B. pertussis infection was more severe in C3H/HeJ than in C3H/HeN mice. Surprisingly, Ab- and Ag-specific IFN- responses were enhanced at the peak of infection, whereas Ag-specific IL-10-producing T cells were significantly reduced in C3H/HeJ mice. This was associated with enhanced inflammatory cytokine production, cellular infiltration, and severe pathological changes in the lungs of TLR4-defective mice. Our findings suggest that TLR-4 signaling activates innate IL-10 production in response to B. pertussis, which both directly, and by promoting the induction of IL-10-secreting type 1 regulatory T cells, may inhibit Th1 responses and limit inflammatory pathology in the lungs during infection with B. pertussis.
PUBLISHED
Keywords: Biochemistry